Synthesis, Characterization and Antimicrobial Activity of Dioxouranium(VI) Complexes with Schiff Base Ligand Containing Indole Ring - RAJENDRAN, G.; ABHILASHA, A. (Asian Journal of Chemistry, 2010)
Complexes of dioxouranium(VI) with the Schiff base derived from indole-2,3-dione (isatin) and hydrazine have been synthesized and their physico-chemical properties investigated using elemental analysis, molar conductance and spectral analysis (IR, UV-Visible and 1H NMR). Various anions such as acetate, lactate, nitrate, perchlorate, sulphate and thiocyanate act as secondary ligands by coordinating to the metal ion. Mixed ligand complexes of UO2(VI) with dimethyl sulfoxide or diphenyl thiourea and isatin-3-hydrazone have been synthesized and characterized. The ligand and some of the complexes were screened for their antibacterial and antifungal activities towards Staphylococcus aureaus, Pseudomonas aeruginosa, Escherichia coli, Cryptococcus neoformans and Candida albicans